Um imaginário de identificação com a literatura de autoajuda - Silva, Gabriela Belo da (2012)
This research approaches self-help literature as a modeling practice that is crossed by socio-historical and ideological issues, that through the Subjectitudinal1 Enunciative Imaginary Representations (REIS), build a discursivity that induces the Reader Subject Instance (ISL) to look for a paradigm of unique subject, center of its speech, and able to, by itself, becomes a happy instance in contemporary time. We had as approach to understand and analyse discursive working of Brilliant Parents, Fascinating Teachers (2003), written by Jorge Augusto Cury, as well as the discourses that emerge from this discursivity. For this research, REIS have allowed the establishment of a real imaginary which produces in Reader Subject Instance (ISL) an effect of uniqueness and individuation from interdiscourse simulation in intradiscourse. It was by the investigation of the language while discursive materiality that analyses has been built, through operating-utterances, working with Matrix Dispositive, developed by Santos (2004), concerned to N-essence Dispositive in double-vector. In this way, we try to investigate and hypothesize impacts and dislocations from this discursivity in Subjectitudinal identity constitution Reader Subject Instance (ISL) especially teachers as discursive subject in formation or already formed. Then, to do this research, we are supported by French Discourse Analysis, specifically in Michel Pêcheux´s no notions of subject, discoursive place, identification and sense, in Mikhail Bakthin´s concepts of chronotop and exotopy in interface with the analytic philosophic, and some principles of Relativity Theory, founded by Einstein, and later, reported by Capra (1989). Analysis has showed that Cury´s discursive practice of self-help was built to reinforce the capitalist market through high consumption of this type of literature by the use of surplus-value. It is the creation and mediation of the REIS that contribute with the construction and marketing of illusions, in a game of meanings, based in an essentially ideological practice, that are projected in the subject´s actions on the/in language. Throughout this research, we could verify that this discursivity woks from the ISL´s desires and beliefs, which allowed us to understand this discourse in a didactic way, since it has as focus to direct and to shape conduct. Thus, there is no consideration of incompleteness, heterogeneity and moving constitutive of the subject, factor that contributes to the omission of the corporate and ideological subject, since it is in ISL´s unknown ideological that the identification process is established. Consequently, while assimilating what is objective (in ISL´s real) and turn into essentially subjective REIS (by literature´s real), Author Subject Instance (ISA) aims to discipline the subjects, pointing out ways in order to get an homogeneous behavior. The ISA´s preference is to construct a logical positivist subject. Then, it is through the ISL´s illusion of autonomy that this discursivity suggests a hygienization of thought, to erase the knowledge learned in the universities, since these knowledge, according to ISA, produce only lots of stones , in other words, theories that are useless in practice.